نباتات کی ضرورت و اہمیت اور مسلمانوں کی خدمات نباتات'ایک تحقیقی جائزہ - Abroo Kalsoom; Sobia Khan (Pakistan Journal of Islamic Research)
Plants are the most important source of God's blessing and survival, without which life is not only difficult but impossible, the main source of human nutrition and the beauty of our planet. The mention of plants in the Qur'an and Hadith increases their importance and usefulness. Even the Holy Prophet planted fruits, flowers, vegetables and trees with his blessed hand and described their properties, for this reason Muslims also turned their creativity towards them and wrote many books and articles on them. Duties such as tree planting were performed until no Muslim period was devoid of botanical services. In view of this importance, the botanical services of Muslims have been described in this paper. We tend to forget the importance of plants and often take them for granted. You may think there is nothing much to the plants and trees that are around us every day but they are vital for life and our long-term survival. Plants are an essential resource - we rely on them for food, water, medicine, the air we breathe, habitat, our climate and more.